Artificial Intelligence and Teacher Creativity in Center-Based Early Childhood Learning: A Qualitative Study at PG-TKIT 2 Qurrota A’yun Ponorogo - Harisma Fatihatul Hayyu; Dyah Worowirastri Ekowati; Mohammad Syahri (Journal of General Education and Humanities, 2026)
This study examines early childhood teachers’ creativity in AI-supported center-based learning at PG-TKIT 2 Qurrota A’yun Ponorogo. It applies a descriptive qualitative approach within a constructivist paradigm. Data were collected through participatory observation, semi-structured interviews, and documentation involving six classroom teachers and one school leader. Data were analyzed using thematic analysis based on creativity indicators from J. P. Guilford and E. Paul Torrance, including fluency, flexibility, originality, elaboration, and evaluation. The findings indicate that integrating AI tools such as ChatGPT-4o and Google Gemini appears to enhance teachers’ creativity across the planning, implementation, and evaluation stages. In planning, AI supports rapid idea generation and variation. During implementation, it facilitates adaptive and multimodal learning aligned with children’s needs. In evaluation, AI contributes to more comprehensive and data-informed assessment practices. AI is also used to generate personalized learning content, including simple narrative adaptations based on children’s experiences, which strengthens engagement and contextual relevance. Overall, AI integration contributes to increased student participation, more diverse learning activities, and improved instructional efficiency. However, several challenges remain, including the risk of overdependence on AI, the need to verify content accuracy, and unequal parental digital literacy. These findings imply that AI should function as a supportive pedagogical tool rather than a substitute for teacher judgment. Strengthening teacher training and establishing ethical guidelines are essential to ensure responsible AI use in early childhood education.